Antiprotozoal activities of Triterpenic Acids and Ester Derivatives Isolated from the Leaves of Vitellaria paradoxa - Catteau, Lucy; Schioppa, Laura; Beaufay, Claire; Girardi, Cynthia; Hérent, Marie-France; Frédérich, Michel; Quetin-Leclercq, Joëlle (Planta Medica, 2020)
Leaves of Vitellaria paradoxa, also called “Shea butter tree”, are used in traditional medicine to treat various symptoms including malaria fever, dysentery, or skin infections. Composition of the dichloromethane extract of V. paradoxa leaves possessing antiparasitic activities was investigated. Five pentacyclic triterpenic acids together with 6 ester derivatives were isolated and identified by standards comparison, MS and 1H-NMR analysis. Corosolic, maslinic, and tormentic coumaroyl esters and their corresponding triterpenic acids were isolated from this plant for the first time. The antiparasitic activities of the 11 isolated compounds were evaluated in vitro on Plasmodium falciparum, Trypanosoma brucei brucei, and Leishmania mexicana mexicana and their selectivity determined by cytotoxicity evaluation on WI38 cells. None of the isolated compounds showed good antiplasmodial activity. The antitrypanosomal activity of individual compounds was in general higher than their antileishmanial one. One isolated triterpenic ester mixture in equilibrium, 3-O-p-E/Z-coumaroyltormentic acids, showed an attractive promising antitrypanosomal activity (IC50 = 0.7 µM) with low cytotoxicity (IC50= 44.5 µM) compared to the corresponding acid. Acute toxicity test on this ester did not show any toxicity at the maximal cumulative dose of 100 mg/kg intraperitoneally on mice. In vivo efficacy evaluation of this compound, at 50 mg/kg by intraperitoneal route on a T. b. brucei-infected mice model, showed a significant parasitemia reduction on day 4 post-infection together with 33.3% survival improvement. Further bioavailability and PK studies are needed along with mode of action investigations to further assess the potential of this molecule.
Keywords: Vitellaria paradoxa; Sapotaceae; parasites; triterpenic esters; antitrypanosomal; natural compounds